Direito, política, autoritarismo e democracia no Brasil: da Revolução de 30 à promulgação da Constituição da República de 1988 - Cristiano Paixão (Araucaria)
There were authoritarian and democratic constitutions in Brazilian politic and legal history. The focus of this essay will be on 1930-1945 and 1964-1988 periods. Constitutional history is here produced emphasizing the relationship between politics and law. The authoritarian experience post-1930 is stressed, particularly on the 1937-1945 years. In the following section, the essay intends to analyze the military dictatorship in Brazil (1964-1985) under a conceptual point of view. The confl icting projects at that time - on the constitution and the political transition - are emphasized. In the conclusive remarks, the essay intends to demonstrate some risks and challenges for contemporary constitutionalism, especially under the 1987-1988 constitution-making process.